Prerequisites for successful succession in family company according to its successor - Dzwigol-Barosz, Mariola (Managerial Economics, 2019)
The aim of this paper was to indicate prerequisites for successful succession in a family company from the successor’s point of view. The author presented the methods used to assess the conditions of the succession process with the use of observations and an individual semi-structured interview. Particular emphasis was placed on the influence of being brought-up in an entrepreneurial family on the further development of the successor’s professional career. Special consideration was given to finding out why a successor chose a particular area of edu-cation and what the parents’ influence on was shaping his/her entrepreneurial attitudes. The author underlined the role of emotional intelligence, as the latter is a part of the successor’s competencies. In this field, the author defined the competencies that are of crucial importance for the given process. The author enumerated factors affecting the succession process to the greatest extent, and the key role of the senior member in ensuring the continuity of the family company was also shown. Furthermore, the paper indicated the course of the succession process in the family business, as the former should be a comprehensive, long-term, and meticulously planned process in which (apart from the formal requirements and competencies) one should take into consideration family values, rules of the behavior and traditions of the company.